2016
DOI: 10.4103/0970-9371.175490
|View full text |Cite
|
Sign up to set email alerts
|

Utility of fine-needle aspiration cytology in the identification of parathyroid lesions

Abstract: Objectives:Fine-needle aspiration cytology (FNAC) is a first-line investigation in the evaluation of neck nodules. In an attempt to search for reliable cytomorphological criteria for parathyroid lesions, we systematically evaluated cytomorphology of FNAC of parathyroid lesions.Study Design:FNAC of 15 parathyroid and 15 hyperplastic thyroid nodules with histological confirmation were reviewed for following features: Cellularity, follicles, bare nuclei, cohesiveness, vascular profiles, cytoplasmic granularity, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 9 publications
(27 reference statements)
5
36
0
Order By: Relevance
“…All samples were submitted as a thyroid nodule FNA, and represented 0.12% of the total thyroid FNAs examined over this period. Using previously published criteria, 47 samples (78%) displayed cytologic findings that were suggestive of PT cells, and were subsequently confirmed with IHC. Thirteen (13) samples (22%) had cytologic features that were not recognized as PT on initial ThinPrep evaluation and were classified using TBSRTC criteria as either AUS or SFN.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…All samples were submitted as a thyroid nodule FNA, and represented 0.12% of the total thyroid FNAs examined over this period. Using previously published criteria, 47 samples (78%) displayed cytologic findings that were suggestive of PT cells, and were subsequently confirmed with IHC. Thirteen (13) samples (22%) had cytologic features that were not recognized as PT on initial ThinPrep evaluation and were classified using TBSRTC criteria as either AUS or SFN.…”
Section: Resultsmentioning
confidence: 98%
“…The cytologic features of parathyroid (PT) cells have been well described, both in conventional smears and in liquid‐based preparations . However, ectopic PT within the thyroid gland can be difficult to recognize, as both are neuroendocrine glands and show similar cytologic features . About 30% of these ectopic nodules are asymptomatic, and clinical and radiologic identification may also be difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Common major cytomorphologic features of parathyroid tissue that have been reported in the literature include a papillary-like pattern with fibrovascular cores or prominent vascular network/proliferation, stippled chromatin, follicular pattern, and bare nuclei (Table 5). 2,[4][5][6][7][8][9][18][19][20][21][22] The majority of these studies also concluded that a combination of cytomorphologic features supported by either ancillary studies or correlation with clinical, radiologic, and laboratory findings are important in establishing a correct diagnosis of parathyroid tissue. The main diagnostic features in the current study also included bare nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…Dimashkieh and Krishnamurthy reported that nuclei measuring smaller than thyroid follicular cells, bare nuclei, stippled chromatin, and a prominent vascular network with adherent cells indicated parathyroid origin . Another study found vascular proliferation, bare nuclei, intracytoplasmic fat vacuolation, and high cellularity to be significantly associated with parathyroid origin …”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation